Privilege or Mandate? Nepo Babies in Biblical Narrative and the Political Reality of Indonesia - Obet Nego; Debby Christ Mondolu (DIEGESIS: Jurnal Teologi Kharismatika, 2026)
This article examines the phenomenon of nepo babies, a term denoting the children of prominent figures who attain power through family connections, in relation to biblical narrative and Indonesia's political realities. Employing a critical qualitative approach combining biblical hermeneutics with critical discourse analysis, the study finds that political dynasties in Indonesia expose a persistent tension between privilege and mandate. Though often defended as legitimate within existing legal and social frameworks, such dynasties frequently erode democracy and deepen social inequality. A parallel pattern emerges in Scripture: hereditary succession alone guarantees neither competence nor faithfulness, as the failures of Eli's sons and Solomon's decline make clear, whereas Joseph and David show that legitimate leadership rests on divine calling and integrity rather than lineage. Drawing on Walter Brueggemann's prophetic imagination, the article argues that the church is called to function as a prophetic community that criticizes unjust power structures and envisions more just political alternatives. It concludes that privilege should be understood as a divine mandate rather than an inherited entitlement, with implications for ecclesial public engagement and a more meritocratic Indonesian politics. AbstrakArtikel ini mengkaji fenomena nepo babies, istilah yang merujuk pada anak dari tokoh berpengaruh yang memperoleh kekuasaan melalui koneksi keluarga, dalam kaitannya dengan narasi Alkitab dan realitas politik Indonesia. Dengan pendekatan kualitatif kritis yang menggabungkan hermeneutika biblika dan analisis wacana kritis, penelitian ini menemukan bahwa dinasti politik di Indonesia memperlihatkan ketegangan yang terus-menerus antara privilese dan mandat. Meski sering dibela sebagai sah dalam kerangka hukum dan sosial yang berlaku, dinasti semacam ini kerap melemahkan demokrasi dan memperlebar ketimpangan sosial. Pola serupa muncul dalam Kitab Suci: suksesi berdasarkan garis keturunan saja tidak menjamin kompetensi maupun kesetiaan, sebagaimana terlihat dari kegagalan anak-anak Eli dan kejatuhan Salomo, sementara Yusuf dan Daud menunjukkan bahwa kepemimpinan yang sah berakar pada panggilan ilahi dan integritas, bukan pada garis keturunan. Dengan mengacu pada imajinasi profetis Walter Brueggemann, artikel ini menegaskan bahwa gereja dipanggil menjadi komunitas profetis yang mengkritik struktur kekuasaan yang tidak adil sekaligus membayangkan tatanan politik alternatif yang lebih adil. Artikel ini menyimpulkan bahwa privilese seharusnya dipahami sebagai mandat ilahi, bukan hak warisan, dengan implikasi bagi keterlibatan publik gereja dan politik Indonesia yang lebih meritokratis.